Multiple Controls on the Accumulation of Organic-Rich Sediments in the Besa River Formation of Liard Basin, British Columbia, Canada - Jiyoung Choi; Hyun Suk Lee; Yuri Kim; Omid H. Ardakani; Sung Kyung Hong (Geofluids)
The Late Devonian Besa River Formation is an organic-rich shale sequence in Liard Basin, northeastern British Columbia, Canada, with significant natural gas reserves. High-resolution elemental geochemistry of three long continuous cored intervals of the Besa River Formation was used to better understand the paleodepositional environment of organic-rich intervals in this thick marine shale. The studied core intervals were divided into five chemostratigraphic units based on organic and inorganic geochemical proxies. The highest total organic carbon (TOC) content (up to 13 wt.%) was identified in the upper part of the Patry member (Unit III) within the Liard Basin. During the deposition of Unit III, low clastic influx and euxinic bottom conditions mostly contributed to the high accumulation of organic carbon. Moreover, a high productivity and organic influx may have increased organic-rich basinal sediments, which further depleted the seawater column oxygen content in the presence of a large amount of organic matter. This took place within the oxygen-deficient bottom water from the Patry–Exshaw stratigraphic units. This high TOC interval was most likely deposited through abundant biogenic silica production by radiolarians, thereby utilizing the supply of nutrients from the upwelling. Sea level change was also an important factor that controlled organic matter accumulation in the Besa River Formation. The transgression in sea level changed the residence time of the organic matter in oxic zones within the water column, which limited its supply in deeper water; this decreased the TOC content in Unit IV. Before the deposition, silica production collapsed and was replaced by terrestrial sedimentation of clay minerals in the upper part of the Exshaw member, which caused organic matter dilutions in Unit V (under 5 wt.%). These results provide new insights into the effects of relative sea level changes on redox conditions, productivity, and detrital flux, which are related to organic matter enrichment patterns and their geographic variations. Unit III is characterized by an organic-rich interval as well as an abundance of biogenic silica that is closely related to fracturing. Thus, Unit III is expected to have the highest shale gas potential in the Devonian Besa River Formation. The high-resolution geochemical data integrated with well log and/or seismic data can be used to determine the distribution of the perspective interval for shale gas production in the Liard Basin.